2007
DOI: 10.1002/art.22719
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of rheumatoid arthritis patients to changing therapy: Discordance between disease activity and patients' treatment choices

Abstract: Objective. Despite advances in rheumatoid arthritis (RA) treatment, patients' decisions regarding therapy often deviate from expert recommendation. This study was undertaken to investigate patients' acceptance and satisfaction with therapy, willingness to change therapy, and reasons for not changing.Methods. Participants (n ‫؍‬ 6,135) completed an 11-item questionnaire concerning treatment preferences. Eight questions assessed reasons for not wanting to change therapy. The contribution of individual predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 31 publications
4
118
1
1
Order By: Relevance
“…Numerous reports have documented poor patient acceptance of expensive RA therapies and poor adherence to therapy 19. Assessment of joint temperature may help to identify patients with progressive, destructive RA who would benefit most from expensive, effective biologic therapy 2.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have documented poor patient acceptance of expensive RA therapies and poor adherence to therapy 19. Assessment of joint temperature may help to identify patients with progressive, destructive RA who would benefit most from expensive, effective biologic therapy 2.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is concordant with the results of a large study comprising over 6,000 patients, where more than three-fourths of the patients were satisfied with their therapy, but the majority of those patients had moderate or even high arthritis activity. 17 Satisfaction with RA control and risk of side effects were the dominant cause of unwillingness to change the therapy. 17 In another study, 65% of 97 patients with moderate to high disease activity did not want to change their current medications.…”
Section: Discussionmentioning
confidence: 99%
“…17 Satisfaction with RA control and risk of side effects were the dominant cause of unwillingness to change the therapy. 17 In another study, 65% of 97 patients with moderate to high disease activity did not want to change their current medications. Major causes of unwillingness to change were satisfaction with current disease state and perceived risk of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients are more strongly invited to participate in the decision to decrease or stop their medication, because it is more preference sensitive. Previous studies have shown that patients fear returning symptoms (in the case of remission) or unknown side effects (when changing therapy) (119,120). More research is necessary to clarify why patients feel they are too much involved in the decision to decrease or stop medication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patient participation is important because studies show that patients' and rheumatologists' beliefs about illness and treatment may differ. This includes how they rank the potential benefits and side effects of available treatment options and how they prioritize long-term outcomes (120,(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139). Therefore high quality patient-physician communication about the choice of treatment is important.…”
Section: Introductionmentioning
confidence: 99%